IMPACTS OF COVID-19 PANDEMIC ON PSYCHOLOGICAL AND SOCIO-EMOTIONAL BEHAVIOUR AMONG MEDICAL HEALTHCARE PROFESSIONALS IN UNIVERSITY OF ABUJA TEACHING HOSPITAL, ABUJA, NIGERIA - Dr. HARUNA, O. Idris; ZUBAIR, T. Hassan (Scholar Express Journals, 2021)
The research examined the impacts of covid-19 pandemic on the psychological and socio-emotional behaviour among medical healthcare professionals in University of Abuja teaching hospital, Abuja, Nigeria. The research used descriptive survey design. The research population constituted all medical healthcare professional (i.e doctors, nurses and laboratory scientists) in University of Abuja Teaching Hospital (UATH) in Gwagwalada Area Council, Federal Capital Territory (FCT), Abuja. The instrument use for data collection was self-structured questionnaire. The questionnaire was titled: Socio-Emotional Behaviour Questionnaire (SEBQ), Anxiety Questionnaire (AQ) and Stress Questionnaire (SQ). The data collected was analyzed using descriptive statistics. Pearson Product Moment Correlation (PPMC). The hypotheses were tested at 0.05 level of significant. The results of the findings revealed among others: there was significant relationship between psychological impact of COVID-19 pandemic and socio-emotional behaviour (coefficient .001, p<0.05), anxiety (coefficient .000, p<0.05) and stress (coefficient .000, p<0.05). The study therefore, recommends that affected vulnerable medical healthcare professionals will need to be screened to detect their mental health problems. Frontline staff should be engage with modern equipment such as  screening tools, special clinics and retraining programme will be necessary to improve the psychological out-come.
Keywords: COVID-19 Pandemic; Psychological; Socio-emotional Behaviour; medical healthcare professionals